STUDENTS' REPRESENTATION IN SOLVING WORD PROBLEM - Ardhi Sanwidi (Jurnal Infinity, 2018)
The purpose of this research is to describe the representation of sixth grade students in solving mathematics word problems. The focus of the representation of this research is an external representation which is viewed from students with high mathematical abilities. The method used in this research is task-based interview, by giving a problem test of word problems. Students who have a high level of abilities, he makes pictures of all problems and successfully solve the problems. Students whose level of abilities is lacking, he only makes incomplete symbol / verbal representations, he has wrong when solving the problems. Various kinds of representations and increasing abilities in many problems such as multiplying exercises and solve the word pronlem. Applying various representations to students are very important to be improved by students in order to succeed in solving various mathematical word problems.